Exploration of Flora Diversity and Recommending Species for Reclamation of Coal Mining with Biodiversity Concept in Besiq Bermai Forest, East Borneo - Trimanto Trimanto; Siti Sofiah (Journal of Tropical Life Science, 2018)
This research was conducted to gather basic information to support recovery coal mining area with study of flora biodiversity. Plants inventory were conducted explorative in Besiq Bermai forest. Some observations were conducted on plants as integral part of the documentation process. The result showed that there are 203 numbers of plant. They consist of 51 families of flora collection to be conserved in Purwodadi Botanic Garden. There are 53 species of orchid that collected from this forest, including of rare species and endemic orchid. There are 70 numbers of 1000 specimen floras to be collected in Nursery of coal mining to be used in reclamation program. There are 20 species of flora that be conserved because it is threatened species that based on IUCN. Ten species can be chosen to become pioneer species in reclamation of coal mining area. Biodiversity concept can be used in reclamation of post mining area. Prospective conservation area that called Arboretum is provided for in-situ conservation program. Some practical considerations are suggested for fu-ture reclamation projects.